1986
DOI: 10.1007/bf00925100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diethylcarbamazine on microfilariae ofLitomosoides carinii in vitro and in vivo

Abstract: Culture-derived Litomosoides carinii microfilariae (MFF) were used in in vitro and in vivo systems to investigate the effect of diethylcarbamazine (DEC) on these MFF. In vivo: Male rats, Mastomys natalensis, all of the same age, were injected intrathoracically (12) or intraperitoneally (36) with 10(3) or 10(4) MFF. After 30 min one half of each group of rats was given DEC per os. At 30, 60, and 120 min after DEC administration, two rats from the treated and two from the untreated group were bled and killed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Clearly, in comparing different systems a variance of outcomes of this nature often occurs. Weiner, Abraham & D'Antonio (1986) reported that adhesion of M. natalensis peritoneal exudate cells to Mf in vitro was enhanced fourfold on addition of serum from normal rats which had received DEC in vivo. No effect was seen on adding DEC directly to the in vitro assay, whether alone or in conjunction with normal serum.…”
Section: Dec Promotion Of Host Cell Adhesionmentioning
confidence: 99%
“…Clearly, in comparing different systems a variance of outcomes of this nature often occurs. Weiner, Abraham & D'Antonio (1986) reported that adhesion of M. natalensis peritoneal exudate cells to Mf in vitro was enhanced fourfold on addition of serum from normal rats which had received DEC in vivo. No effect was seen on adding DEC directly to the in vitro assay, whether alone or in conjunction with normal serum.…”
Section: Dec Promotion Of Host Cell Adhesionmentioning
confidence: 99%
“…Where appropriate laboratory models of human parasite species are unavailable or unable to generate sufficient material, closely related animal parasite species have been used as alternatives For example, in drug discovery against filarial species a multitude of animal infections such as Acanthocheilonema viteae, Litomosoides carinii, Onchocerca lienalis and O. gutturosa have been employed . Recent success demonstrating this has come with the evaluation of O. gutturosa and O. lienalis for screening antibiotics for anti‐ Wolbachia /filarial activity .…”
Section: Helminth Screening Strategiesmentioning
confidence: 99%